Problem Kompatibilitas Pemberian Obat secara Intravena pada Pasien di Intensive Care Unit - Haqoiroh; Rahmawati, Fita; Azhar Syed Sulaiman, Syed (Jurnal Farmasi (Journal of Pharmacy), 2018)
Intravenous administration of drugs is commonly used in hospitals patients who need rapid pharmacological effects or when patients can not take oral administration. Preparation for intravenous administration of drugs need special condition because there are some risks include incompatibilities. The aim of this study is to investigate the prevalence of intravenous drug incompatibilities such as drug incompatibilities in Intensive Care Units patients at RSUP Dr. Sardjito and UGM Hospital, and to find the risk factor that affect of drug incompatibilities such as length of hospital stay, number of drugs, and caused of hospitalization.This study was a cross-sectional, prospective, and multicenter in RSUP. Dr. Sardjito and Academic UGM Hospital, Yogyakarta. The location of this study were in ICU, ICCU, and HCU. The prevalence of potential drug incompatibility were analyzed with description statistics and the association between potential incompatibilities and risk factors will be investigated using student t test and ANOVA with 95% confidence interval. 65 patients were collected from this research. The prevalence of potential drug incompatibilities (PI) were found in 28 prescriptions with ratio PI 2.4 incompatibility/patient. The highest incompatibility type was precipitation of 42 (83,35%) and the most precipitating drug pairs are fentanyl and phenytoin; midazolam and phenytoin. The number of drugs were significantly related with PI.